Developing underpass park at Ampang-Kuala Lumpur Elevated Highway (Akleh) to change unutilized space into community space by using Low Impact Development (L.I.D) method. - Syed Aziz, Syed Mohammad Fadhil (2018)
In the modernization and development of a city, there is an area that becomes idle area where it has potential to be a dark spot for crime activities. The idle areas include abandoned space and idle space that lead to social and environmental issues. The purpose of the community park design and the recreation area is to make the area an idle green area, which will be an attraction for the community to encourage outdoor activities that stimulate to the healthy lifestyle The main purpose of this study is to develop an abandoned space into a public and community recreation area. Site study are basically located under the elevated highway (underpass) where has been identified as sensitive area. Based on inventory and analysis phase, the site study has been classified as reserved area where the river base has been fully concreted to construct the floodplain to decrease the possibility of flooding during storm and heavy rain. The main issue of this site study is disconnectivity space where has been separated by existence of the elevated highway structure and concrete base river. To connect the space, author need to create an adjacent green spaces to bring the community to the proposed area.